Biodegradable polymer composites used in rapid prototyping technology by Melt Extrusion Polymers (MEP) - Bulanda, Katarzyna; Oleksy, Mariusz; Oliwa, Rafał; Budzik, Grzegorz; Przeszłowski, Łukasz; Mazurkow, Aleksander (Polimery, 2020)
Appropriate selection of polymeric materials enables their wide application not only in machine construction elements, suspension and interior equipment of vehicles. Simultaneously with the development of new polymer materials, the processes of their processing developed. This also applies to incremental technologies. Rapid prototyping methods using 3D printers are largely based on various types of polymer materials. Currently, 3D printing is a well-known technique for producing functional elements, especially the Melt Extrusion Polymers (MEP) method, which is the oldest of the known techniques of spatial production. The main reason of the technology is designing and then manufacturing parts for many fields, including engineering, medicine, as well as the automotive and aviation industries. The article is a review of the literature on the use of composites based on thermoplastic polymers to develop new polymer materials used for 3D printing by MEP.